(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2023)
Phyllodes tumors are rare fibroepithelial tumors that account for less than 0.5% of all breast tumors. Presentation in children is even rarer. In this paper, we describe a case of an 11-year-old adolescent girl with a benign phyllodes tumor. The rare presentation at this age, its distinguishing features, the preoperative diagnostic difficulties, and the management protocols, surgical resection and reconstructive approach of this uncommon tumor may provide useful insight and perspective for patients and clinicians facing similar challenges in the paediatric population. Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 50-52